Silicon-carbon negative electrode material prepared based on biomass hard carbon as well as preparation method and application of silicon-carbon negative electrode material
By using biomass hard carbon silicon carbon negative electrode material in lithium-ion batteries, the problem of expansion and contraction of silicon carbon materials in lithium-ion batteries is solved, and the battery stability and circulation performance are achieved. The process is simple and environmentally friendly. , reduces costs.
Patent Information
- Application Number
- CN202411197964.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2024-12-13
AI Technical Summary
The existing lithium battery silicon carbon anode materials have problems of expansion and contraction during charging and discharging, resulting in insufficient battery stability and cycle life. The existing modification methods are complex, costly and at risk of environmental pollution.
Using biomass hard carbon impregnated with dilute solution of silicon source as a carrier, biomass hard carbon silicon carbon negative electrode material is prepared by in-situ reduction, and the rich pore structure of biomass hard carbon such as coconut shell charcoal makes the silicon components evenly distributed, combined with High-temperature calcination treatment to prepare a silicon-carbon negative electrode material with an optimized structure.
The working efficiency and safety performance of lithium-ion batteries are improved, the preparation cost is reduced, and the material's capacity and circulation performance are significantly improved. The battery charge and discharge expansion are limited in the material pores, extending the battery's service life.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium battery negative electrode materials, and specifically relates to a silicon-carbon negative electrode material prepared based on biomass hard carbon, and a preparation method and application thereof. Background Art
[0002] As one of the typical symbols of the green and new energy era, the advent of lithium-ion battery technology has undoubtedly provided great convenience for human society. Lithium-ion batteries have the advantages of high energy density, long cycle life, and good safety performance. They are gradually being widely used in a variety of mobile electronic devices and electric vehicles. At the same time, people's requirements for the energy density and cycle life of lithium-ion batteries are constantly increasing. Therefore, it is urgent to develop a new generation of electrode materials to improve the overall performance of lithium batteries. With the growing global demand for renewable resources, various forms of low-cost carbon elements have gradually become a new type of energy storage material due to their high energy density, long cycle life, and environmental friendliness. They are widely used in lithium-ion batteries and other fields. The theoretical gram capacity of carbon, which is often used as a negative electrode material, is 372mA‧h / g, and there are a large number of micropores and mesopores on the surface. These pores will expand and shrink during the battery charging and discharging process, resulting in battery capacity decay, and even causing serious battery safety problems. At the same time, single silicon is widely used as one of the best negative electrode materials for high-capacity lithium-ion batteries because of its high theoretical gram capacity (about 4200mA‧h / g) and low lithium absorption voltage (about 0.5V). However, silicon also has a large volume change during the battery's charge and discharge process, which leads to severe cracking and crushing of silicon, easily causing damage to the electrode structure, constantly exposing the new surface of the material to the electrolyte, and reducing battery performance.
[0003] In order to solve the above problems, physical or chemical methods are usually used in the prior art to modify carbon and silicon materials to reduce their surface porosity and improve the stability of the battery. At the same time, there are also studies to improve the electrochemical properties of silicon materials by doping other elements or forming composite materials. In "Preparation of Phosphorus-based Negative Electrode Materials for Lithium / Sodium Ion Batteries by Ball Milling", Zhang Miao used a one-step plasma ball milling method to prepare antimony nanocrystals / phosphorus-carbon (Sb / PC) composite materials, so that antimony nanocrystals are evenly distributed in the amorphous PC matrix, and the phosphorus component and the carbon component are connected by carbon-phosphorus bonds. The uniformly distributed Sb nanocrystals in the material can activate the P component, and the carbon-phosphorus bonds formed in the plasma spherical graphite process can enhance the structural resistance of the material to volume stress during the electrochemical reaction process, which has certain effects on improving the battery specific capacity and cycle stability. Chinese patent CN116314719A discloses a silicon-carbon composite negative electrode material comprising graphite, nano-silicon coated with an amorphous carbon layer formed by phenolic resin-derived carbon, and an amorphous carbon matrix prepared by mechanical fusion and rolling technology, which has relatively high first coulomb efficiency and long cycle stability. Patent CN117865150A provides a method for preparing a high mesoporous carbon material by mixing, drying, inert gas carbonization, cooling, washing, and drying biomass powder, silicone-modified styrene-acrylic emulsion, surfactant, and sodium hydroxide solution as raw materials, and then mixing the obtained high mesoporous material with graphite and silicon powder to prepare a silicon-carbon composite negative electrode material. The patent with publication number CN117577816A uses monosilane as a silicon source gas and ethylene as a carbon source gas to co-deposit porous carbon-based materials to obtain a silicon-carbon negative electrode material precursor, and then carbon-coates it to obtain a silicon-carbon negative electrode material.
[0004] The existing technology has solved the problem of silicon-carbon negative electrode materials to a certain extent, but there is still a gap in the requirements for actual applications. First, the existing modification methods often fail to achieve the expected effect in eliminating the pore efficiency of carbon materials, resulting in large rate expansion and contraction problems in the battery during the charging and discharging process. Secondly, although the existing methods for modifying silicon materials have improved the electrochemical performance of batteries to a certain extent, these methods are often complex in process, high in cost, and have the risk of secondary pollution to the environment. Therefore, how to effectively optimize the overall structure of lithium battery silicon-carbon negative electrode materials while taking into account both low cost and environmental protection, so that the expansion of the carbon negative electrode during the charging and discharging process is limited to the pores of the material, and the battery capacity and cycle performance are further improved, is a problem that needs to be urgently solved by technical personnel in this field. Summary of the invention
[0005] In order to solve the problems that the internal crystal arrangement of hard carbon is disordered, the interlayer spacing is larger than that of graphite carbon, it has a larger pore structure and a lower redox potential, the present invention provides a silicon-carbon negative electrode material based on biomass hard carbon and a preparation method and application thereof. The silicon-carbon negative electrode material prepared from biomass hard carbon is prepared by using inexpensive and easily available coconut shell charcoal that will not graphitize at high temperatures as a carrier, and is immersed in a dilute silicon source solution at low temperature, and then reduced in situ to obtain the silicon-carbon negative electrode material. The silicon-carbon negative electrode material is applied to lithium-ion batteries to improve the battery working efficiency and safety performance.
[0006] The present invention is achieved through the following technical solutions: A method for preparing a biomass hard carbon silicon carbon negative electrode material comprises the following steps: (1) Activation of hard carbon: immerse the hard carbon in an acid I solution, heat it to 60-80°C under stirring and keep it warm for 10-24 hours, filter and wash it until it is neutral to obtain activated hard carbon; (2) Silicon source adsorption: Step (1) immersing the activated hard carbon in a silicon source aqueous solution system for 6 to 8 hours to allow the silicon source to be adsorbed into the micropores of the hard carbon to form a hard carbon adsorption material, which is then filtered; (3) In-situ acidification of the adsorbent material: The hard carbon adsorbent material after filtration in step (2) is rinsed with an acid II solution, immersed in an acid III solution containing a dispersant for 2 to 4 hours, filtered, and washed with water until it is neutral and the metal ion content is less than 50 ppm, thereby obtaining a hard carbon material with in-situ acidification of the adsorbent silicon source; (4) High temperature calcination: In an inert gas and hydrogen atmosphere, the hard carbon material acidified by adsorbing the silicon source in situ in step (3) is gradually heated to 1200-1600°C and kept warm, and then cooled and ground to obtain a biomass hard carbon silicon-carbon negative electrode material.
[0007] Furthermore, in step (1), the concentration of the acid I solution is 0.5-2.0 mol / L; in step (3), the mass percentage concentration of the acid II solution is 50-80%, and the mass percentage concentration of the acid III solution is 5-20%.
[0008] Furthermore, the acid I solution in step (1) is one or more of hydrochloric acid, sulfuric acid, and nitric acid; the acid II solution in step (3) is one of formic acid and acetic acid aqueous solution; the acid III solution is one of formic acid, acetic acid or carbonic acid aqueous solution, preferably carbonic acid aqueous solution.
[0009] Furthermore, in step (1), the hard carbon is biomass carbon, and the hard carbon particle size distribution range is D 50 =20~100μm; the silicon source aqueous solution in step (2) is sodium silicate Na with a modulus n of 1.0~3.5 2 O‧nSiO 2 aqueous solution; the dispersant in step (3) is one of sodium polyacrylate, polyacrylic acid and polyethylene glycol.
[0010] Furthermore, the biomass carbon in step (1) is one of coconut shell, straw and rice husk; and the mass percentage concentration of the silicon source aqueous solution in step (2) is 5-30%.
[0011] Furthermore, in step (1), the mass ratio of hard carbon to acid I solution is 1:1-8; in step (2), the mass ratio of activated hard carbon to silicon element in silicon source aqueous solution is 0.8-2.4:1; in step (3), the mass ratio of hard carbon adsorbent to acid III solution is 1:2-10, and the concentration of dispersant in acid III solution for impregnation is 50-200 ppm.
[0012] Furthermore, in step (4), the volume ratio of the inert gas to hydrogen is 3 to 10:1.
[0013] Furthermore, in step (4), the heating rate is 5-8°C / min, the holding time is 3-5h, and the particle size distribution after grinding is D50 of 12-16μm and D90 of 25-28μm.
[0014] In the present invention, the biomass hard carbon silicon carbon negative electrode material is prepared by the preparation method.
[0015] In the present invention, the biomass hard carbon silicon carbon negative electrode material is used in lithium ion batteries.
[0016] The lithium-ion battery includes the biomass hard carbon silicon carbon negative electrode material prepared above, a conductive additive and a binder, wherein the conductive additive is at least one of graphite, conductive carbon black, and carbon nanotubes, or a mixture of two of them; the binder can be selected from any one of carboxymethyl cellulose CMC, polyvinylidene fluoride PVDF, and polyvinyl fluoride PVF, or a mixture of at least two of them; the mass ratio of the biomass hard carbon silicon carbon negative electrode material, the conductive additive, and the binder is 90~100:4~6:1~2. Beneficial Effects
[0017] (1) The present invention uses natural biomass hard carbon with rich pore structure such as coconut shell and straw as precursor, and immerses it in water glass aqueous solution with different modulus to make it adsorb sufficient silicon source. This method can ensure the uniform distribution of silicon source in the pores of hard carbon, and effectively improve the specific capacity of silicon-carbon composite negative electrode material; (2) The present invention effectively "embeds" the silicon component into the pores of the porous hard carbon matrix by subjecting the water glass adsorbed in the hard carbon pores to in-situ acidification and high-temperature reduction treatment, and uses the porous carbon matrix skeleton structure to confine the silicon component, so that the expansion generated during the battery charging and discharging process is confined in the hard carbon pores, thereby improving the battery's operating efficiency and safety performance;
[0018] (3) The preparation method of the biomass hard carbon silicon-carbon negative electrode material of the present invention is simple, safe and environmentally friendly, which greatly reduces the manufacturing cost. The prepared biomass hard carbon silicon-carbon negative electrode material has a better gram capacity and improved first-time efficiency. Under the action of the dispersant, the silicon component is more evenly embedded in the pores of the hard carbon skeleton structure, so that the expansion generated by the battery charging and discharging process is limited in the hard carbon pores through the cooperation of silicon, which greatly reduces the volume expansion of the battery caused by repeated use. DETAILED DESCRIPTION
[0019] In order to illustrate the beneficial effects of the present invention, further explanation is given below in conjunction with specific embodiments, but it is not limited to the contents of the specification.
[0020] The preparation method of the hard carbon in the following embodiments and comparative examples is as follows: 500g of coconut shell charcoal is ground with a high-speed Chinese medicine grinder, and three batches (a total of 1500g) are ground. The particle sizes after grinding are D50=43.6μm, D50=34.2μm, and D50=45.5μm, respectively. After mixing, it is used as hard carbon.
[0021] The dispersant in the following examples and comparative examples is polyacrylic acid (PAA) with a weight average molecular weight of 9963. The inert gas is high-purity nitrogen. Example 1
[0022] (1) Activation of hard carbon: 200 g of hard carbon and 600 g of acid I solution (0.5 mol / L hydrochloric acid) were added to a mixing kettle, stirred, heated to 62±2°C, kept warm for 10 h, cooled to below 30°C, filtered, and the filter cake was sprayed with deionized water to wash until the pH value of the filtrate was 6.82. The filter cake was dried at 50°C and crushed to obtain activated hard carbon, weighing 198.9 g; (2) Silicon source adsorption: The activated hard carbon prepared in step (1) and 3200 g of silicon source aqueous solution (15% by mass fraction of Na 2 O·1.5SiO 2 ) into the kettle, stirred for 10 minutes, allowed to stand and soak for 6 hours, and then filtered. (3) The filter cake in step (2) was washed with 200 g of acid II solution (50% by mass acetic acid) each time. After 5 washes, the filter cake was dried at 50°C and crushed. The weight was 215.7 g and transferred to a mixing kettle. 650 g of acid III solution (10% by mass carbonic acid) with a PAA content of 80 ppm was added. After stirring for 10 min, the mixture was allowed to stand for 2 h, filtered, and washed with deionized water until the pH value was 6.92 and the metal ion content was less than 50 ppm, thereby obtaining a hard carbon material with in-situ acidification of adsorbed silicon source; (4) High-temperature calcination: The hard carbon material that has been in-situ acidified by adsorbing silicon source is placed in a calcination furnace. The air is first replaced by nitrogen, and then part of the nitrogen is replaced by hydrogen to make the volume ratio of nitrogen and hydrogen in the furnace be 6:1. Then, the temperature is raised to 1200°C at a rate of 5°C / min and kept at this temperature for 3 h. After cooling to room temperature, the material is taken out and ground to a particle size of D50 = 13.6 μm and D90 = 25.8 μm, obtaining 215.4 g of biomass hard carbon silicon-carbon negative electrode material. Example 2
[0023] (1) Activation of hard carbon: 200 g of hard carbon and 1000 g of acid I solution (2 mol / L hydrochloric acid) were added to a mixing kettle, stirred, heated to 78±2°C, kept warm for 24 h, cooled to below 30°C, filtered, and the filter cake was sprayed with deionized water to wash until the pH value of the filtrate was 6.79. The filter cake was dried at 50°C and crushed to obtain activated hard carbon, weighing 199.1 g; (2) Silicon source adsorption: The activated hard carbon prepared in step (1) and 2000 g of silicon source aqueous solution (with a mass fraction of 20% Na 2 O·1.5SiO 2 ) into the kettle, stirred for 10 minutes, allowed to stand and soak for 8 hours, and then filtered. (3) The filter cake in step (2) was washed with 200 g of acid II solution (80% by mass acetic acid) each time. After 5 washes, the filter cake was dried at 50°C and crushed. The weight was 216.0 g and transferred to a mixing kettle. 1080 g of acid III solution (10% by mass carbonic acid) with a PAA content of 100 ppm was added. After stirring for 10 min, the mixture was allowed to stand for 2 h, filtered, and washed with deionized water until the pH value was 6.83 and the metal ion content was less than 50 ppm, thereby obtaining a hard carbon material with in-situ acidification of adsorbed silicon source; (4) High-temperature calcination: The hard carbon material that has been in-situ acidified by adsorbing silicon source is placed in a calcination furnace. The air is first replaced by nitrogen, and then part of the nitrogen is replaced by hydrogen to make the volume ratio of nitrogen and hydrogen in the furnace 8:1. Then, the temperature is raised to 1600°C at a rate of 8°C / min and kept at this temperature for 5 h. After cooling to room temperature, the material is taken out and ground to a particle size of D50 = 14.1 μm and D90 = 27.3 μm, obtaining 215.8 g of biomass hard carbon silicon-carbon negative electrode material. Example 3
[0024] (1) Activation of hard carbon: 200 g of hard carbon and 600 g of acid I solution (0.5 mol / L nitric acid) were added to a mixing kettle, stirred, heated to 62±2°C, kept warm for 10 h, cooled to below 30°C, filtered, and the filter cake was sprayed with deionized water to wash until the pH value of the filtrate was 6.87. The filter cake was dried at 50°C and crushed to obtain activated hard carbon, weighing 198.5 g; (2) Silicon source adsorption: The activated hard carbon prepared in step (1) and 2867 g of silicon source aqueous solution (15% by mass fraction of Na 2 O·2SiO 2 ) into the kettle, stirred for 10 minutes, allowed to stand and soak for 6 hours, and then filtered. (3) The filter cake in step (2) was washed with 200 g of acid II solution (50% by mass acetic acid) each time. After 5 washes, the filter cake was dried at 50°C and crushed. The weight was 215.5 g and transferred to a mixing kettle. 650 g of acid III solution (10% by mass carbonic acid) with a PAA content of 80 ppm was added. After stirring for 10 min, the mixture was allowed to stand for 2 h, filtered, and washed with deionized water until the pH value was 6.88 and the metal ion content was less than 50 ppm, thereby obtaining a hard carbon material with in-situ acidification of adsorbed silicon source; (4) High-temperature calcination: The hard carbon material that has been in-situ acidified by adsorbing silicon source is placed in a calcination furnace. The air is first replaced by nitrogen, and then part of the nitrogen is replaced by hydrogen to make the volume ratio of nitrogen and hydrogen in the furnace be 6:1. Then, the temperature is raised to 1200°C at a rate of 5°C / min and kept at this temperature for 3 h. After cooling to room temperature, the material is taken out and ground to a particle size of D50 = 14.4 μm and D90 = 26.1 μm, obtaining 215.7 g of biomass hard carbon silicon-carbon negative electrode material. Example 4
[0025] (1) Activation of hard carbon: 200 g of hard carbon and 1000 g of acid I solution (2 mol / L nitric acid) were added to a mixing kettle, stirred, heated to 78±2°C, kept warm for 24 h, cooled to below 30°C, filtered, and the filter cake was sprayed with deionized water to wash until the pH value of the filtrate was 6.90. The filter cake was dried at 50°C and crushed to obtain activated hard carbon, weighing 198.2 g; (2) Silicon source adsorption: The activated hard carbon prepared in step (1) and 1789 g of silicon source aqueous solution (20% by mass fraction of Na 2 O·1.5SiO 2 ) into the kettle, stirred for 10 minutes, allowed to stand and soak for 8 hours, and then filtered. (3) The filter cake in step (2) was rinsed with 200 g of acid II solution (80% by mass acetic acid) each time. After 5 rinses, the filter cake was dried at 50°C and crushed. The weight was 215.3 g and transferred to a mixing kettle. 1075 g of acid III solution (10% by mass carbonic acid) with a PAA content of 100 ppm was added. After stirring for 10 min, the mixture was allowed to stand for 4 h, filtered, and washed with deionized water until the pH value was 6.86 and the metal ion content was less than 50 ppm, thereby obtaining a hard carbon material with in-situ acidification of adsorbed silicon source; (4) High-temperature calcination: The hard carbon material that has been in-situ acidified by adsorbing silicon source is placed in a calcination furnace. The air is first replaced by nitrogen, and then part of the nitrogen is replaced by hydrogen to make the volume ratio of nitrogen and hydrogen in the furnace 8:1. Then, the temperature is raised to 1600°C at a rate of 8°C / min and kept at this temperature for 5 h. After cooling to room temperature, the material is taken out and ground to a particle size of D50 = 12.6 μm and D90 = 25.9 μm, obtaining 215.3 g of biomass hard carbon silicon-carbon negative electrode material.
[0026] Comparative Example 1 Without using silicon source aqueous solution for impregnation, other conditions were the same as in Example 1, and 215.8 g of biomass hard carbon negative electrode material with particle size D50=14.9 μm and D90=26.2 μm was obtained.
[0027] Comparative Example 2 No dispersant was added to the acid III solution, and other conditions were the same as in Example 1, to obtain 215.6 g of biomass hard carbon silicon carbon negative electrode material with a particle size of D50 = 13.3 μm and D90 = 26.4 μm.
[0028] Performance Test: 1. The physical and chemical properties of the biomass hard carbon silicon carbon negative electrode materials prepared in Examples 1-4 and Comparative Examples 1-2 were tested in accordance with the national standard GB / T43114-2023 for hard carbon negative electrodes. The results are shown in Table 1: Table 1 Physical and chemical properties of hard carbon negative electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 2
[0029] Electrochemical performance testing of hard carbon negative electrode materials: 2. According to the method provided by the national standard GB / T43114~2023 for hard carbon negative electrodes, button batteries were prepared and performance tested. When making the negative electrode of the button battery, the following raw materials and mass ratios were used: 96% carbon silicon negative electrode material, 1wt% Cabot carbon black REGAL330R, 1.5wt% carboxymethyl cellulose (CMC) and 1.5wt% styrene butadiene latex (SBR). When the carbon silicon negative electrode material prepared in Examples 1~4 and Comparative Examples 1~2 was used as the raw material to prepare the negative electrode of the button battery, the electrochemical performance test results are shown in Table 2 below: Table 2 Electrochemical performance test results of button batteries
[0030] It can be seen from Table 1 and Table 2 that the carbon-silicon negative electrode material obtained by modifying hard carbon with a silicon source has a better gram capacity than the traditional hard carbon negative electrode material, and the first efficiency is also improved. Under the action of the dispersant provided by the present invention, the silicon-doped hard carbon negative electrode material can make the silicon component more evenly embedded in the pores of the hard carbon skeleton structure, so that the expansion generated by the battery charging and discharging process is limited in the hard carbon pores through the cooperation of silicon, which greatly reduces the volume expansion of the battery caused by repeated use. Without the use of a dispersant, the increase in gram capacity and the reduction in battery expansion rate are also obvious, but the effect is not as good as when a dispersant is used.
[0031] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a biomass hard carbon silicon carbon negative electrode material, characterized in that: The following steps are involved: (1) Activation of hard carbon: immerse the hard carbon in an acid I solution, heat it to 60-80°C under stirring and keep it warm for 10-24 hours, filter and wash it until it is neutral to obtain activated hard carbon; (2) Silicon source adsorption: Step (1) immersing the activated hard carbon in a silicon source aqueous solution system for 6 to 8 hours to allow the silicon source to be adsorbed into the micropores of the hard carbon to form a hard carbon adsorption material, which is then filtered; (3) In-situ acidification of the adsorbent material: The hard carbon adsorbent material after filtration in step (2) is rinsed with an acid II solution, immersed in an acid III solution containing a dispersant for 2 to 4 hours, filtered, and washed with water until it is neutral and the metal ion content is less than 50 ppm, thereby obtaining a hard carbon material with in-situ acidification of the adsorbent silicon source; (4) High temperature calcination: In an inert gas and hydrogen atmosphere, the hard carbon material acidified by adsorbing the silicon source in situ in step (3) is gradually heated to 1200-1600°C and kept warm, and then cooled and ground to obtain a biomass hard carbon silicon-carbon negative electrode material.
2. The method for preparing the biomass hard carbon silicon carbon negative electrode material according to claim 1, characterized in that: The concentration of the acid I solution in step (1) is 0.5-2.0 mol / L; the mass percentage concentration of the acid II solution in step (3) is 50-80%, and the mass percentage concentration of the acid III solution is 5-20%.
3. The method for preparing the biomass hard carbon silicon carbon negative electrode material according to claim 1, characterized in that: In step (1), the acid I solution is one or more of hydrochloric acid, sulfuric acid, and nitric acid; in step (3), the acid II solution is one of formic acid and acetic acid aqueous solution; and the acid III solution is one of formic acid, acetic acid, or carbonic acid aqueous solution, preferably carbonic acid aqueous solution.
4. The method for preparing the biomass hard carbon silicon carbon negative electrode material according to claim 1, characterized in that: In step (1), the hard carbon is biomass carbon, and the hard carbon particle size distribution range is D 50 =20~100μm; the silicon source aqueous solution in step (2) is a sodium silicate Na2O‧nSiO2 aqueous solution with a modulus n of 1.0~3.5; the dispersant in step (3) is one of sodium polyacrylate, polyacrylic acid and polyethylene glycol.
5. The method for preparing the biomass hard carbon silicon carbon negative electrode material according to claim 4, characterized in that: The biomass carbon in step (1) is one of coconut shell, straw and rice husk; the mass percentage concentration of the silicon source aqueous solution in step (2) is 5-30%.
6. The method for preparing the biomass hard carbon silicon carbon negative electrode material according to claim 1, characterized in that: In step (1), the mass ratio of hard carbon to acid I solution is 1:1-8; in step (2), the mass ratio of activated hard carbon to silicon element in silicon source aqueous solution is 0.8-2.4:1; in step (3), the mass ratio of hard carbon adsorbent to acid III solution is 1:2-10, and the concentration of dispersant in acid III solution for impregnation is 50-200 ppm.
7. The method for preparing the biomass hard carbon silicon carbon negative electrode material according to claim 1, characterized in that: In step (4), the volume ratio of the inert gas to hydrogen is 3 to 10:
1.
8. The method for preparing the biomass hard carbon silicon carbon negative electrode material according to claim 1, characterized in that: In step (4), the heating rate is 5-8°C / min, the holding time is 3-5h, and the particle size distribution after grinding is D50 of 12-16μm and D90 of 25-28μm.
9. A biomass hard carbon silicon carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the biomass hard carbon silicon carbon negative electrode material according to claim 9 in a lithium ion battery.
Citation Information
Patent Citations
Silicon-carbon composite negative electrode material, preparation method and application thereof, and lithium ion battery
CN116314719A
Silicon-carbon negative electrode material and preparation method and application thereof
CN117577816A
Preparation method of mesoporous carbon material with high mesoporous rate and application of mesoporous carbon material in silicon-carbon negative electrode
CN117865150A
